Recent advances in systems, control and information technology : proceedings of the International Conference SCIT 2016, May 20-21, 2016, Warsaw, Poland - Szewczyk, Roman; Kaliczyńska, Małgorzata (Advances in intelligent systems and computing, 2017)
This book presents the proceedings of the International Conference on Systems, Control and Information Technologies 2016. It includes research findings from leading experts in the fields connected with INDUSTRY 4.0 and its implementation, especially: intelligent systems, advanced control, information technologies, industrial automation, robotics, intelligent sensors, metrology and new materials. Each chapter offers an analysis of a specific technical problem followed by a numerical analysis and simulation as well as the implementation for the solution of a real-world problem.